Perspectives in newborn screening for SCID in Japan. Case report: newborn screening identified X-linked severe combined immunodeficiency with a novel IL2RG variant - Beppu, Shiro; Nishikawa, Takuro; Tomomasa, Dan; Hijikata, Atsushi; Kasabata, Hiroshi; Terazono, Hideyuki; Ikawa, Kazuro; Nakamura, Tatsuro; Horikawa, Shogo; Nagahama, Jun; Nakamura, Aki; Abematsu, Takanari; et al. (Frontiers in Immunology, 2024)
BackgroundNewborn screening (NBS) for severe combined immunodeficiency (SCID) has improved the prognosis of SCID. In Japan, NBS testing (measurement of the T-cell receptor excision circles (TREC) and kappa-deleting recombination excision circles (KREC)) was launched in 2017 and has expanded nationwide in recent years. In this study, we report a Japanese patient with X-linked SCID with a novel IL2RG variant identified through NBS. The patient underwent cord blood transplantation (CBT).CaseThe patient had no siblings or family history of inborn errors of immunity. He was born at 38 weeks of gestation and weighed 3,072 g. His NBS results revealed TREC 0 copies/105 cells (normal value: >565 copies/105 cells), which was considered suggestive of SCID. The patient was referred to our hospital. Although his lymphocyte count was 1,402/μL, naïve T cells and CD56+ natural killer (NK) cells were decreased to 0% and 0.05% of the total lymphocytes, respectively. Flow cytometric measurement testing revealed a decrease in γc protein expression in the B lymphocytes and NK lymphocytes. We identified a hemizygous novel missense variant (c.256A>C, p.Thr86Pro) of IL2RG. Both in silico and structural analyses revealed that this variant is likely pathogenic. At 3 months of age, he underwent CBT from a human leukocyte antigen-full-matched unrelated donor. The conditioning regimen included fludarabine (180 mg/m2) and targeted busulfan (35 mg×h/L). The patient achieved high-level donor chimerism and immune reconstitution, including B-cell function, at 13 months.ConclusionUsing NBS, the patient was diagnosed as having X-linked SCID with a novel missense variant of IL2RG. Early diagnosis using NBS tests enables safe hematopoietic stem cell transplantation without complications such as infection. We also found that even SCID with novel variants can be accurately diagnosed using the NBS program. In Japan, the test uptake rate is approximately 80% due to the high number of self-funded screening tests, and it is hoped that the uptake rate will increase in the future.